Effects of Finasteride on Apoptosis and Regulation of the Human Hair Cycle - Sawaya, Marty E.; Blume-Peytavi, Ulrike; Mullins, Diane L.; Nusbaum, Bernard P.; Whiting, David; Nicholson, Donald W.; Lotocki, George; Keane, Robert W. (Journal of cutaneous medicine and surgery, 2002)
A number of studies have provided evidence that apoptosis is a central element in the regulation of hair follicle regression. In androgenetic alopecia (AGA), the exact location and control of key players in the apoptotic pathways remains obscure. In the present study, we used a panel of antibodies and investigated the spatial and cellular pattern of expression of caspases and inhibitors of apoptosis (IAPs), such as XIAP and FLIP, in men with normal scalp and in men with AGA before and after 6 months of treatment with 1 mg oral finasteride treatment. Constitutive expression of caspases-1, -3, -8, and -9 and XIAP was detected predominantly within the isthmic and infundibular hair follicle area, basilar layer of the epidermis, and eccrine and sebaceous glands. AGA-affected tissues showed an increase in caspase (-1, -3, -6, -9) immunoreactivity with a concomitant decrease in XIAP staining. After 6 months of finasteride treatment, both caspases and XIAP were similar to levels exhibited by normal subjects. Immunoblot analysis was performed to determine antibody specificity and cellular expression of caspases. Purified populations of keratinocytes, melanocytes, dermal papilla, and dermal fibroblasts derived from human hair follicles were cultured in vitro and treated with 0.5 mm staurosporin. Time-course experiments revealed that processing of caspase-3 is a principal event during apoptosis of these hair cell types. These data suggest that alterations in levels of caspases and IAPs regulate hair follicle homeostasis. Moreover, finasteride appears to influence caspase and XIAP expression in hair follicle cells thus signaling anagen, active growth in the hair cycle.